Empowered - Warren, Adam 1967- (Dark Horse Books, 2007)
"Not only is the costumed crimefighter "Empowered" saddled with a less-than-ideal superhero name, but she wears a skintight and cruelly revealing "supersuit" that only magnifies her body-image insecurities. Worse yet, the suit's unreliable powers are prone to failure, repeatedly leaving her in appallingly distressing situations-- and giving her a shameful reputation as the lamest "cape" in the masks-and-tights business"--Page 4 of cover
Keywords: Women heroes / Comic books, strips, etc; Heroes / Comic books, strips, etc; Comic books, strips, etc / United States; USA; Comic